2002
DOI: 10.1046/j.1365-2389.2002.00424.x
|View full text |Cite
|
Sign up to set email alerts
|

Aggregate strength and mechanical behaviour of a sandy loam soil under long‐term fertilization treatments

Abstract: Summary Current concern for soil quality has stimulated research on soil biological and chemical properties. In contrast, the mechanical behaviour of soil is somewhat neglected. We have examined the effects on soil mechanical properties of more than 100 years of contrasting fertilization employing three treatments from the Askov long‐term experiment: UNF (unfertilized), NPK (mineral fertilized) and AM (animal manured). We have measured tensile strength of aggregates when air‐dry and when adjusted to −10, −30 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 19 publications
2
49
0
2
Order By: Relevance
“…Relation between the content of clay and OC for a range of Danish surface soils with different soil management. Results on soil physical characteristics were reported for the Group I through Group III soils by Munkholm et al (2001) and Schjønning et al (2002a), the Askov B2 and B4 fields were studied by Munkholm et al (2002), and the Askov B5 soil by Schjønning et al (1994). Soils with poor tilth conditions are shown by closed symbols.…”
Section: The Soil Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…Relation between the content of clay and OC for a range of Danish surface soils with different soil management. Results on soil physical characteristics were reported for the Group I through Group III soils by Munkholm et al (2001) and Schjønning et al (2002a), the Askov B2 and B4 fields were studied by Munkholm et al (2002), and the Askov B5 soil by Schjønning et al (1994). Soils with poor tilth conditions are shown by closed symbols.…”
Section: The Soil Matrixmentioning
confidence: 99%
“…Low levels of soil OM (NCC>0) may create aggregates that are unstable in wet conditions but become hard and strong in dry conditions (Watts and Dexter, 1997;Munkholm et al, 2001Munkholm et al, , 2002Schjønning et al, 2002a). This has major impacts on agronomic aspects like tillage but also on clay dispersibility/colloid mobilization and hence colloidfacilitated transport of environmental pollutants (de Jonge et al, 2004ab).…”
Section: Soil Characteristicsmentioning
confidence: 99%
“…After 30 years of crop rotations, annual SOC gains ranged from 60 to 220 kg per ha per year for fields in Canada (Campbell et al, 2000). Nutrient management through fertilization and manure application generally increases SOC concentration (Haynes and Naidu, 1998;Schjonning et al, 2002;Munkholm et al, 2002;Hao et al, 2002). Manure application increases SOC concentration (Martens and Frankenberger, 1992;Haynes and Naidu, 1998;Nyamangara et al,1999;Aoyama et al, 2000).…”
Section: Mitigation Of Climate Change By Agriculturementioning
confidence: 99%
“…Simansky et al [11] even reported that chemical fertilization (NPK) did not have statistically significant influence on increasing the soil structure stability of orthic luvisol. In addition, organic matter was a major contributor to aggregate stability because it provided important biological binding agents, which decreased the breakdown of aggregates by slaking, swelling, or even osmoting stress [7,[12][13][14]. Some studies have reported that aggregate stability was higher in soil fertilized with manure than in soil fertilized with chemical fertilizers [15][16].…”
mentioning
confidence: 99%